2007
DOI: 10.1111/j.1447-0594.2007.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Klotho gene delivery suppresses oxidative stress in vivo

Abstract: Objective: Mice deficient in the klotho gene exhibit a syndrome resembling premature human aging. A recent report also suggested that klotho transgenic mice exhibited a long lifespan, which shows that klotho is an antisenescence gene. Previously, klotho has been reported to improve endothelial dysfunction, and also to have a preventive effect against oxidative stress. In the present study, we investigated the effect of klotho gene delivery on blood pressure and oxidative stress in vivo. Methods:Klotho plasmid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…It has been shown that the formation and bioavailability of nitric oxide was decreased in old human and animals 6265. On the other hand, it has been shown that the Klotho gene enhanced NO formation in human and animal cells 47,49. Therefore, we can hypothesize that both anti-aging genes and nitric oxide are critical factors of aging development.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown that the formation and bioavailability of nitric oxide was decreased in old human and animals 6265. On the other hand, it has been shown that the Klotho gene enhanced NO formation in human and animal cells 47,49. Therefore, we can hypothesize that both anti-aging genes and nitric oxide are critical factors of aging development.…”
Section: Discussionmentioning
confidence: 97%
“…Ohta et al47 investigated the effect of Klotho gene delivery on blood pressure and oxidative stress in vivo. They found that Klotho gene upregulated MnSOD expression and total SOD activity in the aorta of mice, enhanced nitric oxide production, and downregulated lipid peroxide concentration in serum of mice.…”
Section: Signaling By Reactive Oxygen Species In Gene- and Enzyme-medmentioning
confidence: 99%
“…Our previous study had also demonstrated that FGF1 treatment blocks ER stress and consequently apoptosis of DA neuron during development of Parkinson's disease (PD) . Moreover, FGF23, the FGF family, has also an anti‐oxidative stress activity . Thus, we hypothesized that FGF1‐associated glucose decreases and subsequent reduction of cellular stress is the another potential cellular molecule mechanisms mediating FGF1 treatment forDN.…”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, FGF23, the FGF family, has also an anti-oxidative stress activity. 18,19 Thus, we hypothesized that FGF1-associated glucose decreases and subsequent reduction of cellular stress is the another potential cellular molecule mechanisms mediating FGF1 treatment forDN.…”
mentioning
confidence: 99%
“…24 A previous study reported that klotho gene delivery up-regulates the expression of manganese superoxide dismutase and suppresses oxidative stress in vivo. 25 In addition, circulating …”
Section: Discussionmentioning
confidence: 99%